2019
DOI: 10.1029/2018jb016945
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Intraplate Fault Systems in Australia: The 2012 Thorpdale, Victoria, Seismic Sequences

Abstract: Using a new seismic waveform data set, we locate 234 earthquakes and estimate source parameters (focal mechanisms, magnitude, and stress drop) of the two largest earthquakes (E1 and E2) in the 2012 seismic sequence in Thorpdale, Victoria. The focal mechanisms suggest thrust faulting, consistent with previous observations in southeast Australia. The estimated magnitudes are M w 4.9 ± 0.14 (E1) and 4.3 ± 0.1 (E2). The estimates of stress drop 57 ± 7.4 MPa (E1) and 28 ± 2.4 MPa (E2) reflect strength of faults in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 133 publications
(166 reference statements)
1
4
0
Order By: Relevance
“…So and Capitanio () found that the recurrence interval for faults embedded in a viscous plate was inversely proportional to the viscosity of the host plate. Our hypothesis is also consistent with observed correlations between crustal heat flow and seismicity in SE Australia (Attanayake et al, ; Holford et al, ), as a thinner lithosphere would result in higher crustal heat flow. Notably, one of the most active areas of seismicity in Australia, the Flinders range, does not occur within a high‐attenuation zone.…”
Section: Discussionsupporting
confidence: 92%
“…So and Capitanio () found that the recurrence interval for faults embedded in a viscous plate was inversely proportional to the viscosity of the host plate. Our hypothesis is also consistent with observed correlations between crustal heat flow and seismicity in SE Australia (Attanayake et al, ; Holford et al, ), as a thinner lithosphere would result in higher crustal heat flow. Notably, one of the most active areas of seismicity in Australia, the Flinders range, does not occur within a high‐attenuation zone.…”
Section: Discussionsupporting
confidence: 92%
“…Earthquakes are less likely to occur in the area as seismicity of the region was studied before selection of Pelican field as a storage site. A baseline passive seismic monitoring study (Attanayake et al, 2023) of the area revealed that no seismic activity was recorded within a 10 km radius of the site. Microseismic events are more likely to be recorded when a fluid is injected into an underground reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…However, much lower friction values are suggested in studies of fault reactivation, often less than 0.3 and possibly lower than 0.1 (Middleton & Copley, 2013). For a general study in Australia, one might choose a default value of 0.4 (Attanayake et al., 2019). However, our analysis focuses on the relative influence of stress on fault behavior, eliminating the need for an additional constant term.…”
Section: Methodsmentioning
confidence: 99%